Standards and industrial ontologies as Industry 4.0 enablers - Henning, Gabriela P. (2024)
One of the pillars of the Industry 4.0 paradigm is the vertical and horizontal integration of systems and devices that need to interplay in this digital ecosystem. Interoperability is crucial to attain this ambitious goal. It is the ability of systems to transact with other systems to exchange data, services and coordinate activities in a seamless fashion. In the last decades, industry has pursued technical interoperability by developing and adopting standards. More recently, in the context of Industry 4.0 reference architectures have been proposed, which aim at providing a roadmap for the use of standards in smart factories. Despite their success, standards still present weaknesses that are addressed in this contribution along with the drawbacks of some of the reference architectures. So far, our work has mainly focused on standards ISA-88 and ISA- 95, but it is currently being extended to other ones. On the other hand, industrial ontologies play a key role in reaching semantic interoperability. Unfortunately, each community assumes that the proper strategy to solve this problem is to create its own ad hoc ontology, thereby recreating the initial problem of data siloes but now at the ontology level. The Industrial Ontology Foundry (IOF) is trying to solve this problem by developing a suite of open and principles-based reference ontologies, from which other domain dependent or application ontologies can be derived in a modular fashion, so that they can be reused in various industrial domains. However, this initiative has other weaknesses, which are described and critically addressed in this work.